Strategy for Building a Positive Image Through the Publication of Scientific Works - Fatkhurahman Fatkhurahman; Hadiyati Hadiyati; Idel Waldelmi (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2022)
Unilak's image as a private university in Riau Province is still low in the eyes of the public, this is evidenced by the negative response from prospective students to choose this institution as a place for them to study. Coupled with the negative image that has existed at Unilak for a long time. Therefore, efforts are needed to build a positive image of Unilak, so that prospective students make Unilak their choice to gain knowledge. When viewed from current technological developments and from the point of view of human resource management, lecturers require lecturers to carry out the tri dharma of higher education, one of which is the publication of scientific works which have recently shown dynamic movements. So what is the right strategy to build a positive image of universities through the publication of lecturers' scientific works. In order to obtain the right strategy in this study using a qualitative and quantitative approach, data collection techniques using in-depth interviews and questionnaires, are journal managers and prospective students, external users. Data analysis techniques using qualitative techniques with SWOT analysis. The results show that the strategy of building a positive image of universities through the publication of scientific papers at Lancang Kuning University is by utilizing the strengths they have in capturing existing opportunities, among others through: Utilizing a strong journal management team to apply for online accreditation of national journals in enhancing the image of the institution ; Utilizing a strong journal management team to get citations to improve the institution's image; Utilizing a strong journal management team to boost the institution's image; Leveraging accredited journals in promoting higher accreditation; Utilizing accredited journals in boosting citations; Utilizing accredited journals in boosting the image of the institution; Utilizing quality lecturer publications in unilak journals for journal accreditation applications; Utilizing lecturer publications to get increased institutional citations; and Utilizing lecturer publications in boosting the image of the institution.